Heat transfer characteristics and performance evaluation of water-cooled PV/T system with cooling channel above PV panel - Wu, Shuang-Ying; Chen, Chen; Xiao, Lan (Renewable energy, 2018)
A three-dimensional numerical model of water-cooled PV/T system with cooling channel above PV panel was built to analyze the influences of mass flow rate, cooling channel height, inlet water temperature and solar radiation intensity on heat transfer characteristics of cooling channel and performance of system. The Nusselt numbers of bottom and top surfaces of cooling channel were calculated, and the energy and exergy efficiencies of PV/T system were obtained. Results show that the Nusselt numbers of bottom and top surfaces perform opposite trend along the flow direction, and the convection heat transfer of bottom surface is better than that of top surface for almost all of cases. There is opposite direction of heat transfer within a certain distance from the entrance when inlet temperature of cooling medium is less than ambient temperature. As for system performance, both thermal efficiency and thermal exergy efficiency have greater variation amplitude when compared with electric efficiency and electric exergy efficiency respectively. The overall exergy efficiency of system achieves maximum at the mass flow rate of 0.003 kg/s and cooling channel height of 5 mm. Besides, the performance between the present system and traditional system was compared and some different conclusions have been drawn. •A numerical model of water-cooled PV/T system with cooling channel above PV panel.•The heat transfer characteristics of cooling channel and parametric analysis.•The energy and exergy efficiencies of system and the optimal parameters.•The performance comparison between the present system and traditional system.